2017
DOI: 10.3389/fendo.2017.00098
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Glucagon-Like Peptide-1 on Bone Metabolism and Its Possible Mechanisms

Abstract: The impact of antidiabetic drugs on bone metabolism is drawing increasing attention due to the discovery of a correlation between type 2 diabetes mellitus (T2DM) and osteoporosis. Glucagon-like peptide-1 (GLP-1) receptor agonists are a novel and promising class of drugs for T2DM, which may also have clinical applications in bone tissue disorders. This review examines the impact of GLP-1 on bone metabolism, including enhancement of bone mineral density and improvement of bone quality. However, the precise effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 59 publications
1
41
0
1
Order By: Relevance
“…The effects of GLP‐1 on CT secretion appear to be prominent in rodents as the concentration of the GLP‐1R is higher in thyroid C cells from rodents compared with thyroid C cells from humans. In fact, human C cells have been shown to be less responsive to GLP‐1‐mediated CT release …”
Section: Drugs and Bonementioning
confidence: 99%
“…The effects of GLP‐1 on CT secretion appear to be prominent in rodents as the concentration of the GLP‐1R is higher in thyroid C cells from rodents compared with thyroid C cells from humans. In fact, human C cells have been shown to be less responsive to GLP‐1‐mediated CT release …”
Section: Drugs and Bonementioning
confidence: 99%
“…In obesity, GLP-1 and other protective gut molecules decrease and the process of osteopenia and/or osteoporosis intensifies progression to osteosarcopenia [91]. Insulin resistance increases, advanced glycation end-products are produced, and reactive oxygen species are formed, and these negatively affect the skeletal muscle causing sarcopenia [92][93][94].…”
Section: Osteosarcopenic Obesitymentioning
confidence: 99%
“…Glucagon‐like peptide 1 (GLP‐1) is a 30‐amino acid peptide hormone secreted from L cells of the gastrointestinal mucosa, which acts as a key determinant of blood glucose homeostasis owing to its capabilities to slow gastric emptying, enhance pancreatic insulin secretion, and suppress pancreatic glucagon secretion . Moreover, it was reported that GLP‐1 might enhance bone mineral density and improve bone quality by promoting bone formation and inhibiting bone resorption . GLP‐1 RAs are a new class of anti‐diabetic drugs that mimic the effects of native GLP‐1, lead to robust glycemic control and weight loss, and different GLP‐1 RAs differ in several aspects owing to the difference in molecular structures .…”
Section: Introductionmentioning
confidence: 99%
“…11 Moreover, it was reported that GLP-1 might enhance bone mineral density and improve bone quality by promoting bone formation and inhibiting bone resorption. 12,13 GLP-1 RAs are a new class of anti-diabetic drugs that mimic the effects of native GLP-1, lead to robust glycemic control and weight loss, and different GLP-1 RAs differ in several aspects owing to the difference in molecular structures. 14 However, the effects of GLP-1 RAs on bone fracture remains unclear.…”
Section: Introductionmentioning
confidence: 99%